Efikasi Bioherbisida Fenol Saponin Terhadap Dinamika Gulma Pada Tebu Lahan Kering - Tyas Dwi Chintya; Hidayat Pujisiswanto; Nanik Sriyani; Agus Karyanto; Rusdi Evizal (AgriMalS, 2026)
Weed infestation in sugarcane cultivation is a major production-limiting factor that can reduce crop yield by 24–52%. The development of environmentally friendly weed control alternatives through the use of plant-based herbicides derived from bioactive plant compounds has become an increasingly relevant approach. This study aimed to evaluate the effectiveness of a phenol and saponin based bioherbicide (Herbiocide SL) in suppressing weed growth in dryland sugarcane ecosystems. The research was conducted from August to November 2025 at the Faculty of Agriculture, University of Lampung; the Integrated Laboratory and Technology Innovation Center, University of Lampung; and the sugarcane plantation area of PT. Gunung Madu Plantations, Central Lampung. A field experiment was designed using a Randomized Complete Block Design (RCBD) with four replications and six treatments. The treatments consisted of four bioherbicide dose levels (5, 7.5, 10, and 12.5 L ha⁻¹), one mechanical weeding treatment, and one untreated plot as a control. Observations were conducted on weed community structure before and after application, dry weed biomass, as well as weed coverage and suppression rates. The results confirmed that Herbiocide SL acts as a contact herbicide. All tested dose levels (5–12.5 L ha⁻¹) effectively suppressed weed growth up to eight weeks after application (WAA), while the higher doses (10 and 12.5 L ha⁻¹) maintained their effectiveness up to 12 WAA. These findings provide a field-based scientific foundation for developing more sustainable weed management strategies in sugarcane cultivation in Indonesia.